Heliospheric 3-D MHD ENLIL simulations of multi-CME and multi-spacecraft events - Odstrcil, Dusan (Frontiers in Astronomy and Space Sciences, 2023)
Interpreting multi-spacecraft heliospheric observations of the evolving solar wind (SW) streams with propagating and interacting coronal mass ejections (CMEs) is challenging. Numerical simulations can provide global context and suggest what may and may not be observed. The heliospheric three-dimensional (3D) magnetohydrodynamic (MHD) ENLIL model can provide a near-real-time prediction of heliospheric space weather, and it is used at NASA Community Coordinated Modeling Center (CCMC), NOAA Space Weather Prediction Center (SWPC), and UK Meteorological Office (MetOffice). However, this version does not show its full potential, especially in the case of multi-CME events observed by various spacecraft. We describe tools developed to interpret remote observations and in-situ measurements better and apply them to multi-CME events observed by ACE, STEREO-A, Parker Solar Probe (PSP), BepiColombo, and Solar Orbiter. We present some results on (1) global structures of the SW speed and density at the ecliptic, (2) the evolution of SW parameters at the spacecraft, (3) magnetic field connectivity at the spacecraft, (4) automatic detection of shock parameters and alert plots, and (5) synthetic white-light (WL) imaging. This paper is not on model initialization or analyzing specific CME events, but it describes features not used at space weather prediction centers and provided by NASA/CCMC Run-On-Request service. This paper advertises new tools and shows their benefits when applied to selected heliospheric space weather events observed at near-Earth, PSP, Solar Orbiter, and STEREO-A spacecraft.